Wetlands Management Assessing Risk and Sustainable Solutions - Gökçe, Didem (IntechOpen, 2019)
Wetlands include mangroves, peatlands and marshes, rivers and lakes, deltas, floodplains, rice fields, and even coral reefs. It is known that wetlands are ecologically sensitive systems and the most vulnerable of habitats. Anthropogenic activities (urbanization, water uses, land cover changes, industrial activity, pollution, climatic change, etc.) have direct and indirect effects on wetlands. The evaluation of wetlands with a multidisciplinary perspective in environmental sciences and social sciences provides efficient results. Each chapter takes a crucial look at different approaches to the solution by analyzing wetland problems in the laboratory or in the field and collecting data. The purpose of this book is to help researchers, scientists, and decision-makers utilize a methodology appropriate for a specific problem.